Exploring Historical Traditions in Spatial Planning for Multi-Family Residential Buildings: Menjelajahi Tradisi Sejarah dalam Perencanaan Tata Ruang untuk Bangunan Tempat Tinggal Multi-Keluarga - Keldiyar, Khudayberdiyev; Khosiyat, Tashmatova (Indonesian Journal of Innovation Studies, 2024)
This study delves into the intricacies of spatial planning solutions for various types of residential and public buildings, highlighting a complex workflow in their design. Focusing on multi-family residential buildings, the research primarily considers economic factors during the design process. Specifically, it explores Uzbekistan's unique historical tradition in constructing residential buildings, offering insights into two distinct versions - national and European. Notably, these buildings predominantly feature separate courtyards. Through a comprehensive analysis of goals, methods, results, and implications, this study contributes valuable knowledge to the global discourse on architectural design and spatial planning. Highlights: The study explores the complexity of spatial planning solutions for residential and public buildings. Economic considerations play a crucial role in the design of multi-family residential buildings. Uzbekistan's historical tradition in residential construction reveals unique architectural features. Keywords: Planning Solutions, Residential Buildings, Architectural Design